Differences between Cardiac and Skeletal Troponin Interaction with the Thin Filament Probed by Troponin Exchange in Skeletal Myofibrils - Yang, Zhenyun (The Biophysical Society, 2009)
Troponin (Tn) is the calcium-sensing protein of the thin filament. Although cardiac troponin (cTn) and skeletal troponin (sTn) accomplish the same function, their subunit interactions within Tn and with actin-tropomyosin are different. To further characterize these differences, myofibril ATPase activity as a function of pCa and labeled Tn exchange in rigor myofibrils was used to estimate Tn dissociation rates from the nonoverlap and overlap region as a function of pCa. Measurement of ATPase activity showed that skeletal myofibrils containing >96% cTn had a higher pCa 9 ATPase activity than, but similar pCa 4 activity to, sTn-containing myofibrils. Analysis of the pCa–ATPase activity relation showed that cTn myofibrils were more calcium sensitive but less cooperative (pCa(50) = 6.14, n(H) = 1.46) than sTn myofibrils (pCa(50) = 5.90, n(H) = 3.36). The time course of labeled Tn exchange at pCa 9 and 4 were quite different between cTn and sTn. The apparent cTn dissociation rates were ∼2–10-fold faster than sTn under all the conditions studied. The apparent dissociation rates for cTn were 5 × 10(−3) min(−1), 150 × 10(−3) min(−1), and 260 × 10(−3) min(−1), whereas for sTn they were 0.6 × 10(−3) min(−1), 88 × 10(−3) min(−1), and 68 × 10(−3) min(−1) for the nonoverlap region at pCa 9, nonoverlap region at pCa 4, and overlap region at pCa 4, respectively. Normalization of the apparent dissociation rates gives 1:30:50 for cTn compared with 1:150:110 for sTn (nonoverlap at pCa 9:nonoverlap at pCa 4:overlap at pCa 4) suggesting that calcium has a smaller influence, whereas strong cross-bridges have a larger influence on cTn dissociation compared with sTn. The higher cTn dissociation rate in the nonoverlap region and ATPase activity at pCa 9 suggest that it gives a less off or inactive thin filament. Analysis of the intensity ratio (after a short time of exchange) as a function of pCa showed that cTn had greater calcium sensitivity but lower cooperativity than sTn. In addition, the magnitude of the change in intensity ratio going from pCa 9 to 4 was less for cTn than sTn. These data suggest that the influence of calcium on cTn exchange is less than sTn even though calcium can activate ATPase activity to a similar extent in cTn compared with sTn myofibrils. This may be explained partially by cTn being less off or inactive at pCa 9. Modeling of the intensity profiles obtained after Tn exchange at pCa 5.8 suggest that the profiles are best explained by a model that includes a long-range cross-bridge effect that grades with distance from the rigor cross-bridge for both cTn and sTn.